Technical Difficulties in Biliary Surgery Arising From Overlong Hepatic Duct - Beguiristain, Alberto; Rompani, Omar C; Praderi, Raúl (Cirugía del Uruguay, 1980)
When the confluence of cystic duct and the common hile duct is exceedingly low, pathological significance is nif but it may, however, be the cause of significant operatory difficulties in patients with biliary disease requiring surgery.